2022
DOI: 10.1159/000525038
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Influence on Microtubule-Associated Proteins and Spine Density in Hippocampus: Implications on Learning and Memory

Abstract: The thorny protrusions or spines increase the neuronal surface area, facilitate synaptic interconnections among neurons, and play an essential role in the hippocampus. Increasing evidence suggests that testosterone, the gonadal hormone plays an important role in neurogenesis and synaptic plasticity. The role of testosterone on microtubule-associated proteins on dendritic neurite stability in the hippocampus and its impact on learning disability not elucidated. Adult male Wistar albino rats were randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, various animal studies also support the impact of testosterone on hippocampal synaptic plasticity and, hence, memory and learning [77][78][79][80].…”
Section: Testosterone Impact On Cognition Mood and Energymentioning
confidence: 91%
“…In addition, various animal studies also support the impact of testosterone on hippocampal synaptic plasticity and, hence, memory and learning [77][78][79][80].…”
Section: Testosterone Impact On Cognition Mood and Energymentioning
confidence: 91%
“…Studies in rats have shown that neuron exposure to increased levels of testosterone is associated with increased neuronal spine density in the amygdala and hippocampal pyramidal neurons (Cunningham et al, 2007), with mice studies showing that gonadectomy leads to morphological changes in dendritic spines of hippocampal pyramidal neurons (Li et al, 2012). Overall, these studies and others point to testosterone's key role in neuronal plasticity (Chen et al, 2022;Fester, 2021;Muthu et al, 2022). Human work has been largely consistent with this view, although there is some evidence that the effects of pubertal hormones on neural structure and function might be more nuanced with region-and/or circuit-specificity, interactions with sex, and both increases and decreases in plasticity (Dai & Scherf, 2019;Laube et al, 2020).…”
Section: Introductionmentioning
confidence: 89%
“…Testosterone modulates neuronal function and gene expression underlying behaviours associated with aggression, social interaction and anxiety via actions on androgen receptors (ARs) in brain regions including the amygdala, hypothalamus and thalamus [ 123 ]. Additionally, testosterone depletion has been associated with hippocampal dysfunction and associated learning and memory deficits [ 124 ], as the androgen has been shown to regulate the expression of microtubule-associated protein 2 (MAP2) and postsynaptic density protein 95 (PSD95) [ 125 ], cytoskeletal and postsynaptic proteins respectively, which are essential for synaptic integrity and plasticity.…”
Section: Neuromodulator Function In the Central Nervous System And Dy...mentioning
confidence: 99%